Mauritius : Inclusiveness of Growth and Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2016)
Mauritius is a high middle-income country with low levels of poverty and inequality. The headcount poverty level was 6.9 percent in 2012; measured by the international standard of United States (U.S.) $2 per day (PPP), poverty was less than 1 percent. On inequality, Mauritius also fared well compared to its peer middle-income countries. On the negative side, Mauritius’ growth has not been equally shared, despite the general improvement in welfare. The economy’s polarization was associated with a structural transformation from labor-intensive industries to services and knowledge-intensive industries. Inclusiveness remains the main challenge for the current growth pattern. When Mauritius will be able to become a high-income country will depend on its ability to improve the labor force’s skill set, develop infrastructure, and further improve the business environment to attract foreign direct investment (FDI) and generate domestic investment. Reduction in inequality and boost of shared prosperity will require more growth and a more pro-poor pattern of growth. An increase in female labor force participation, reduction of high youth unemployment rates, improving the efficiency of the social protection system will reduce growing skills mismatch facilitating inclusive growth and eradicating poverty in Mauritius.